The spread of Islam in Central Asia : a comparison with Southeast Asia - Islam, Arshad (OIC Research Centre for Islamic History, Art and Culture and Ministry of Education and Science, Republic of Kazakhstan R.B. Suleimenov Institute of Oriental Studies, 2010)
Since Islam followed in the footsteps of Arab conquerors of Central Asia, it is sometimes heard that the religion was imposed by force on the region. This is a gross misconception unsupported by any historical evidence. The coming of Islam in the whole region took a comparatively short period of time starting in the mid-seventh century. Islam spread in Central Asia in two phases: The first phase began with the coming of Muslim forces under Abdullah ibn Amir in 28/648-49 to Mawara an-Nahr and was continued into the early eighth century by the able Muslim general Qutaybah ibn Muslim. The second phase was largely the work of Muslim merchants and Sufi preachers who came along the silk route. The fundamental precepts, values and guidelines laid down in the Qur’an were adopted in this phase by Central Asian communities. The period of the greatest influence of Islam on Central Asian people was from the ninth to the twelfth centuries. The faith was widely accepted by both the sedentary and the nomadic ‘hordes’ of the Steppes. Just as in the case of Indonesia and Malaysia, trade played a great role in the spread of Islam in Southeast Asia. By the end of the seventh century the Arabs had settled in parts of Sri Lanka, and this was the beginning of Muslim penetration in Southeast Asia. Though inadequate, the extant evidence reveals the existence of Muslim colonies in different parts of the Malay Archipelago before the mass conversion to Islam took place in the thirteenth century. A comparative study of Central Asia and Southeast Asia from the viewpoint of spread of Islam should therefore be of interest to students of history.